High-growth potential startups in Brazil: a guide to women leadership - Burrier, Charlotte Jacqueline (2018)
Women entrepreneurship studies have focused mainly on Small, Medium and MicroEnterprises (SMMEs) with no intention or potential for higher growth. We call this phenomenon traditional entrepreneurship. This study aims to bridge the gap in research by focusing on high-growth women-led businesses and startups. The aim of this study is thus identify the specific challenges that high-growth women entrepreneurs face as compared to those faced by traditional women entrepreneurs. In order to reach the objective, this research starts by analyzing the profile of traditional women entrepreneurs as defined by the current literature and comparing with a sample of 21 high-growth entrepreneurs, respondents of the qualitative survey questionnaire of this study. It further leads an exploratory research through in-depth interviews with seven of the survey respondents to identify key challenges they face through descriptive methods. The study’s findings point out that the main similarity in the traditional and high-growth women entrepreneurs’ profiles is their tendency to have a prior work experience before launching a startup: in both cases, they do not start a business immediately after their studies. The main difference is the level of education and family component: as a rule, high-growth entrepreneurs are more educated and are slower at constituting a family than traditional entrepreneurs. The main differences between the business profiles are the cause for creation (necessity vs opportunity) growth rate (higher in high-growth businesses) and the technology factor (absent in traditional businesses and omnipresent in high-growth businesses). The study further identifies three key challenges to Brazilian women entrepreneurs: barrier to entry into the entrepreneurship career, lack of knowledge in technology and communication management and lack of knowledge as well as network in the finance area.